A study of cashless practice among ACIS students at UiTM Puncak Alam / Yusra Nasuha Yus Arhanum - Yus Arhanum, Yusra Nasuha (2019)
Many country of the world have been used the cashless system in transaction such as United State (US), China, Japan, South Korea, Singapore and many more. Malaysia also is one of the countries that have been used cashless system since 2018. However, Malaysian is still new on using cashless system in transaction not like other countries. Therefore, this study aims for five objectives. Firstly, the objective is to know the concepts of cashless practice in economy and society. Secondly, to know the factors that influences ACIS students using cashless system. Thirdly, to study the effect of ACIS students' daily lives on using cashless system. Fourthly, to determine the understanding about cashless system among ACIS students at UiTM Puncak Alam. Lastly, to implement the cashless practice among ACIS students at UiTM Puncak Alam. In this study, the resarch methodology used is quantitative method. It begins with data collection method based on questionnaire survey. Questionnaire survey were distrubuted where the questions are modified based on the objectives of study. The findings ilustrated a study of cashless practice among ACIS students at UiTM Puncak Alam applied. Some of them are not quite clear about using the cashless in transaction. Therefore, there are some recommendations that can be applied to improve the acknowledgement of this cashless system. In conclusion, the objectives of this study had been successfully achieved.